The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/polb.10705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of block copolymer/ceramic precursor nanocomposites based on a polysilazane

Abstract: The amphiphilic block copolymer poly(isoprene‐block‐ethylene oxide) was used as a structure‐directing agent for a polysilazane preceramic polymer commercially known as Ceraset. Two block copolymers of different molecular weights and poly(ethylene oxide) weight fractions with body‐centered cubic sphere and hexagonal cylinder morphologies were used. To both polymers, 50 wt % of the silazane oligomer (Ceraset) was added. The resulting composites were cast into films and characterized by small‐angle X‐ray scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
0
35
1
Order By: Relevance
“…To this end we first showed that the amphiphilic diblock copolymer polyisoprene-block-poly(ethylene oxide) (PI-b-PEO) can serve as a structure-directing agent for poly (ureamethylvinyl)silazane (PUMVS), commercially known as Ceraset. [14] In 2004 we demonstrated, to the best of our knowledge for the first time, that mesoporous high-temperature ceramic materials stable up to 1 500 8C can be prepared based on a related approach using polyisoprene-blockpoly(dimethylamino ethyl methacrylate) (PI-b-PDMAEMA) as the structure-directing agent for PUMVS. [15] Both the molecular structure of the block copolymer and the preceramic polymer, as well as details of the heat treatment to convert the liquid PUMVS precursor into a ceramic are shown in Figure 1.…”
Section: Full Papermentioning
confidence: 99%
“…To this end we first showed that the amphiphilic diblock copolymer polyisoprene-block-poly(ethylene oxide) (PI-b-PEO) can serve as a structure-directing agent for poly (ureamethylvinyl)silazane (PUMVS), commercially known as Ceraset. [14] In 2004 we demonstrated, to the best of our knowledge for the first time, that mesoporous high-temperature ceramic materials stable up to 1 500 8C can be prepared based on a related approach using polyisoprene-blockpoly(dimethylamino ethyl methacrylate) (PI-b-PDMAEMA) as the structure-directing agent for PUMVS. [15] Both the molecular structure of the block copolymer and the preceramic polymer, as well as details of the heat treatment to convert the liquid PUMVS precursor into a ceramic are shown in Figure 1.…”
Section: Full Papermentioning
confidence: 99%
“…Compared with other synthetic processes, for example, using organic block copolymers as a template, [15,16] the prepared SiCN product exhibited a higher BET surface area with high temperature stability. The observed high BET surface area even at 1400°C clearly demonstrates that an inorganic-organic block copolymer could be the most reliable route with essential design of curing chemistry to prepare versatile mesoporous nonoxide ceramics with excellent thermal stability.…”
mentioning
confidence: 97%
“…[9][10][11][12][13][14] Wiesner and co-workers reported mesoporous SiCN ceramic materials with an organic diblock copolymer amphiphile through the preferential interaction of inorganic precursors. [15,16] On the other hand, the complete removal of an organic template by pyrolysis can cause serious volume shrinkage, which can reduce the mechanical and dimensional stability of the ceramic products obtained. Manners and co-workers reported the formation of nanostructures using poly(ferrocenylethylmethylsilane)-block-poly(styrene) as an organic-organometallic block copolymer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Temple et al [22] have shown pyrolitic formation of ordered nanoscopic, non-oxide ceramic structures from self-assembly of poly(styrene-b-ferrocenylsilane) block co-polymers at 600 1C. Wiesner et al [23] have demonstrated that block co-polymers can be used as structuredirecting agents to template silicon carbonitride ceramic precursors such as polysilazane. However, there are no examples in the published literature showing the ability to maintain nanoscale control of ordered structures up to the extreme temperatures where these materials will be used.…”
Section: The Technology Opportunitymentioning
confidence: 97%